THE INFLUENCE OF NON PHYSICAL WORK ENVIRONMENT AND QUALITY OF WORK LIFE ON EMPLOYEE PERFORMANCE (STUDY AT COMMUNITY HEALTH CENTER/ PUSKESMAS BANJARMASIN INDAH - Muhammad Ary Aprian Noor; Meiske Claudia; Hastin Umi Anisah; Rini Rahmawati (Adisam Publisher, 2025)
The purpose of this research is to investigate the effect of non- physical work environment and quality of work life on employee performance at Community Health Center/Puskemas Banjarmasin Indah. The research method is quantitative using partial least square structural equation modelling analysis with data analysis using Smart PLS 3.0 software. The study involved 30 respondents is a Community Health Center employee. The type of variable scale used is the ordinal scale. The rating scale for each statement uses a rating scale technique with a likert scale type. Offline questionnaires are distributed, the data analysis stage is the outer model test, namely the validity and reliability test and the inner model test, namely the hypothesis test or significance test. The independent variable of this research is nonphysical work environment and quality of work life. The dependent variable is employee performance variable. Offline questionnaires based on the results of research data analysis it was found that nonphysical work environment had a positive and significant effect on employee performance. Quality of work life had a positive and significant effect on employee performance.